A Study on The Independence of Malang Waste Bank (BSM) Based on Swot Analysis - Rahmat Hidayat; Bagyo Yanuwiadi; Budi Prasetyo (Graduate Program, 2017)
The aim of this paper is to know the independence of Malang waste bank based on SWOT analysis. This paper focuses on the BSM condition by analyzing and allocating its internal factors (strengths and weaknesses) as well as external elements (opportunities and threats). An organization is necessary to identify its strength, weakness, opportunities and threats in order to know the solutions which in turn make the organization evolves. SWOT analysis, however, helps to identify quantitavely the BSM real condition by looking for the quadrant position. Seven internal independence-related factors which have been analyzed with SWOTwere: 1) Legal Entity, 2) Organizational Structure, 3) Human resource, 4) BSM enterprises and activities, 5) waste management mechanism,6) infrastucture, 7) BSM finance. There are four external factors: 1) Government role 2) Corporate social responsibility of PT. PLN Chapter East Java 3) Waste market opportunities 4) People participation as BSM customer. The results of quantitative SWOT analysis on internal and external factors were used to find the BSM quadrant position based on the identification total score timed to the determined weight value. According to the SWOT analysis, the BSM recent condition was in quadrant 3, which meant that the organization was in a weak condition but still had theopportunity to grow and to be independent if the strategy was changed.Keywords: BSM Independence, Malang Waste Bank, SWOT Analysis